2014
DOI: 10.1097/iae.0000000000000296
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Duration of Macula-Off Retinal Detachment on Visual Outcome

Abstract: This meta-analysis suggests that scleral buckling for macular detachment must preferably be performed within 3 days to optimize visual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 23 publications
3
70
0
Order By: Relevance
“…Our study suggested that surgery up to 3 days after central VA loss resulted in best FVA (mean FVA of 0.25±0.21 logMAR compared with 0.29±0.24 logMAR in eyes repaired within 10 days (p<0.001)). This is in line with van Bussel et al 3 who showed FVA worsens already significantly after a maximal lag time of 3 days and deteriorates further with longer durations. According to our data, a pairwise comparison of eyes that had surgery at either day 1, 2 or 3 showed no statistically significant difference (p=1.00) in FVA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study suggested that surgery up to 3 days after central VA loss resulted in best FVA (mean FVA of 0.25±0.21 logMAR compared with 0.29±0.24 logMAR in eyes repaired within 10 days (p<0.001)). This is in line with van Bussel et al 3 who showed FVA worsens already significantly after a maximal lag time of 3 days and deteriorates further with longer durations. According to our data, a pairwise comparison of eyes that had surgery at either day 1, 2 or 3 showed no statistically significant difference (p=1.00) in FVA.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, van Bussel et al 3 reviewed articles published from 1995 to October 2013 of patients with macula-off RRD and treated with scleral buckling (SB) or pars plana vitrectomy (PPV). These authors reported a limitation of their study was that there were insufficient data about the final visual acuity (FVA) in patients who received surgery during the first 3 days after onset of central vision loss.…”
Section: Introductionmentioning
confidence: 99%
“…Although the current practice is to focus on early treatment of macula‐ON detachment as reflected by the median we found of 1 day, we should aim at scheduling earlier surgery of recent macula‐OFF detachment (van Bussel et al. ) to bring down the current median of 5 days.…”
Section: Discussionmentioning
confidence: 98%
“…It would thus have been interesting to add the results according to subgroups defined by the duration of macular detachment. 6,7 The location of retinal breaks is usually superior. In most superior RRD treated by vitrectomy and gas tamponade, the prescription of a strict face-down position for only several hours, once, is efficient to prevent the occurrence of a retinal displacement.…”
Section: To the Editormentioning
confidence: 99%